Encapsulating peritoneal sclerosis—a rare but devastating peritoneal disease - Moinuddin, Zia; Summers, Angela; Van Dellen, David; Augustine, Titus; Herrick, Sarah E. (Frontiers in Physiology, 2015)
Encapsulating peritoneal sclerosis (EPS) is a devastating but, fortunately, rare complication of long-term peritoneal dialysis. The disease is associated with extensive thickening and fibrosis of the peritoneum resulting in the formation of a fibrous cocoon encapsulating the bowel leading to intestinal obstruction. The incidence of EPS ranges between 0.7 and 3.3% and increases with duration of peritoneal dialysis therapy. Dialysis fluid is hyperosmotic, hyperglycemic and acidic causing chronic injury and inflammation in the peritoneum with loss of mesothelium and extensive tissue fibrosis. The pathogenesis of EPS however still remains uncertain although a widely accepted hypothesis is the “two hit theory’ where the first hit is chronic peritoneal membrane injury from long standing peritoneal dialysis followed by a second hit such as an episode of peritonitis, genetic predisposition and/or acute cessation of peritoneal dialysis, leading to EPS. Recently, EPS has been reported in patients shortly after transplantation suggesting that this procedure may also act as a possible second insult. The process of epithelial- mesenchymal transition of mesothelial cells is proposed to play a central role in the development of peritoneal sclerosis, a common characteristic of patients on dialysis however its importance in EPS is less clear. There is no established treatment for EPS although evidence from small case studies suggests that corticosteroids and tamoxifen may be beneficial. Nutritional support is essential and surgical intervention (peritonectomy and enterolysis) is the recommended in later stages to relieve bowel obstruction.